Recycling concrete construction and demolition wastes: a financial feasibility model - Farahat Hassanein, Omar (AUC Knowledge Fountain, 2014)
The construction industry is a very dynamic field. Every day new technologies and methods are invented to speed up the process and increase its efficiency. Efficiency briefly is the measure of the resources used with regards to the actual product being produced. Hence, if a project uses fewer resources it will become more efficient. This thesis examines the recycling of concrete construction and demolition (C&D) waste to reuse it as aggregates in other structural applications for projects in Egypt. This study focuses on the technical and financial components of concrete recycling plants emphasizing on the three main types of concrete recycling plants; stationary, mobile and traditional plant settings. All plant types are designed and compared for different types of recycling projects. The machinery used in the plant is being analyzed technically and financially according to capacity, production rate, country of origin, etc. All the data is extracted from experts in the field and evaluated by university professors and engineers from relevant disciplines. The data is gathered from national and international sources, through numerous interviews, meetings and site visits. The following visits were conducted to extract information to be used in the model, a site visit to a stationary plant in Madrid, Spain, recycling research center in Madrid, Spain, site visit to a mobile plant in Paris, France, interview with director of recycled aggregates, Paris, France, and traditional plant in 6th of October, Giza, Egypt. These findings are gathered and grouped to obtain a comprehensive cost-benefit financial model to demonstrate the feasibility of constructing a concrete recycling plant in Egypt. The type currently being implemented is the traditional one, however, according to the calculations of the model presented in this thesis, the mobile type has generated the most profits among the other types, stationary and traditional. Furthermore, a sensitivity analysis is conducted to provide verification on the model. The exercise of the sensitivity analysis is a change in parameters and then the results are logically tested to verify the correctness of the model. Therefore, the sensitivity analysis is conducted on the mobile type by selecting and maneuvering the expense with the highest impact by -20%, -10%, 10% and 20%. The sensitivity analysis showed that administrative, salaries and cost of goods sold expenses had the most impact on the model. Nevertheless, the case study is conducted to validate the model. The case study at hand is the traditional plant of 50 TPH, in 6th of October, Giza, Egypt. The plant's actual revenues, expense and profits are compared with the same result produced from the model. The actual results available are for the first three years. They are close to the forecasted results, more discussion is available in text. Moreover, a developed user friendly model specialized to forecast revenues, expenses and profits is available in soft copy to be used by any user to help him/her in taking decisions related to his/her investment. In addition, a recommendation is presented to guide investors and contractors when choosing the suitable and most profitable type of equipment based on the project type.